Peer-attachment, Emotional intelligence and school adjustment of high ability secondary school students in Oyo State, Nigeria (2020)
Teachers are often indifferent towards high ability students with the misconception that they could sort themselves out hence, they are neglected. This therefore, affects their ability to adapt to the school environment which had been resulting to depression, general anxiety disorder, academic- underachievement and drop-out from school. Previous studies dwelt more on academic performance and adjustment of regular students with little attention on high ability students. This study, therefore, investigated influence of peer-attachment, emotional intelligence and school adjustment of high ability secondary school students in Oyo State, Nigeria. Descriptive survey design of correlational type was adopted. Simple random sampling technique was used to select five local government areas from each of the three senatorial districts in Oyo State. Simple random sampling technique was also used to select two secondary schools from each local government, while purposive sampling technique was used to select 450 high ability students in SSI (184 males and 266 females), based on their scores in Slossan Intelligence test, Achievement test in English Language and Mathematics. Instruments used were Slossan Intelligence Test (r= 0.86); Mathematics Achievement (r=0.72) and English Language Achievement tests (r=0.75) Peer-attachment (r=0.74); and Emotional Intelligence scale (r=0.78) while Pearson product moment correlation was used to analyse the hypotheses formulated at 0.05 level of significance. Special educators and counselling psychologists should take cognizance of these factors while dealing with high ability students who were newly admitted to schools. It was recommended that teachers of high ability students should be updated on the influence which peer-attachment and emotional intelligence have on the school adjustment of high ability students.